Mollusca from a species-rich deep-water Leptometra community in the Alboran Sea - Serge Gofas; Carmen Salas; José Luis Rueda; Jesús Canoura; Carlos Farias; Juan Gil (Scientia Marina, 2014)
An exceptional species richness for Mollusca was found on Avempace bank (349-365 m), Djibouti group, Alboran Sea, where the most abundant species was the crinoid Leptometra phalangium. A sample of sediment sieved on a 0.5-mm mesh yielded 156 species of molluscs (83 live-taken, 1772 specimens) with a high Shannon-Wiener diversity index (H’(log2)=3.60). The dominant mollusc was Limopsis aurita and the six most common species accounted for 77% of the specimens. On the other hand, 42 species were represented by only one or two specimens. Two species are described as new, three more are first findings in the Mediterranean and two are first findings in Iberian waters. One-third of the species have not been reported from the neighbouring, well-explored Alboran Island platform. There is a considerable balance between the trophic groups, denoting a stable and structured community. Most of the species have an extensive Atlantic range, and most have a planktonic larval stage. Therefore, it can be hypothesized that the fauna benefits from a diverse influx of larvae carried in by the more superficial incoming Atlantic current. Because of its exceptional richness, this type of bathyal community with Leptometra and Limopsis should be considered a high priority for habitat conservation in the Mediterranean deep sea.